Different Methods of Canine Retraction- Part 1 - Mohammed Nahidh; Yassir A. Yassir; Grant T McIntyre (Journal of Baghdad College of Dentistry, 2022)
Background: This review aimed at explaining different methods of canine retraction along the archwire. Methods: Searching for different methods of canine retraction using fixed orthodontic appliances was carried out using different databases, including PubMed Central, Science Direct, Wiley Online Library, the Cochrane Library, Textbooks, Google Scholar, Research Gate, and hand searching from 1930 till February 2022. Results: After excluding the duplicate articles, papers describing the methods of canine retraction along the archwires were included. The most commonly used methods are NiTi closed coil spring and elastic chain. Conclusions: Various methods of canine retraction along the archwires were explained in detail regarding their advantages, disadvantages, and comparisons among different methods supported by clinical trials, systematic review, and meta-analysis. The preferred method is canine retraction with NiTi closed coil spring with 150 and 200 gm. Elastic chain is considered an alternative, low-cost option.